The SAGE Handbook of Conflict Communication : Integrating Theory, Research, and Practice. - Oetzel, John G. (SAGE Publications, 2013)
This second edition of the award-winning The SAGE Handbook of Conflict Communication emphasizes constructive conflict management from a communication perspective, identifying the message as the focus of conflict research and practice. Editors John G. Oetzel and Stella Ting-Toomey, along with expert researchers in the discipline, have assembled in one resource the knowledge base of the field of conflict communication; identified the best theories, ideas, and practices of conflict communication; and provided the opportunity for scholars and practitioners to link theoretical frameworks and applic.